2019
DOI: 10.1111/cea.13501
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of airway structural changes to blood and bronchoalveolar lavage biomarkers, and lung function abnormalities in asthma

Abstract: Background: Airway structural changes are important in asthma pathology and require further investigations.Objective: We sought to evaluate which computed tomography (CT) indices, bronchial histological traits, or blood and bronchoalveolar lavage (BAL) biomarkers correlate best with lung function abnormalities in asthma. Methods:In 105 white adult asthmatics (53 with a component of fixed airflow obstruction), we determined airway cross-sectional geometry of two proximal (the right upper lobe apical segmental a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 34 publications
1
31
0
Order By: Relevance
“…Some evidence suggests that the degree of type‐2 inflammation in the lower airway and circulation is related to lower airway dysfunction. Kozlik et al 34 found that patients with airflow limitations had greater degrees of eosinophilia in blood and bronchoalveolar lavage samples, and Mauro et al 35 reported that asthma patients with impaired lung function had increased blood Eos numbers and values for fractional exhaled NO (FeNO). Asthma patients with nasal polyps show a more severe type‐2 response than asthma patients without nasal polyps 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Some evidence suggests that the degree of type‐2 inflammation in the lower airway and circulation is related to lower airway dysfunction. Kozlik et al 34 found that patients with airflow limitations had greater degrees of eosinophilia in blood and bronchoalveolar lavage samples, and Mauro et al 35 reported that asthma patients with impaired lung function had increased blood Eos numbers and values for fractional exhaled NO (FeNO). Asthma patients with nasal polyps show a more severe type‐2 response than asthma patients without nasal polyps 35 .…”
Section: Discussionmentioning
confidence: 99%
“…BAZAN-SOCHA et al [99] found that fixed airflow limitation and histological signs of airway remodelling correlated better with computed tomography changes in distal than proximal airways in asthmatic patients. Interestingly, those patients had eosinophilia and higher circulating periostin, but also higher blood neutrophils and circulating ADAM33 [100]. Of note, ADAM33 gene polymorphism has already been associated with asthma [101].…”
Section: Insights In Sad Pathophysiology In Asthma and Copdmentioning
confidence: 88%
“…Kozlik and colleagues have reported a detailed and complex study of airway structure in ~100 asthmatics linking structure, cytokines, biomarkers and lung function in asthma 62 . The findings broadly suggest that remodelling is most closely associated with classic Th2 biomarkers together with systemic neutrophilia and a variety of other inflammatory markers.…”
Section: Asthma and Allergic Rhinitismentioning
confidence: 99%